A high-toughness aqueous binder, preparation method and application thereof, lithium-ion battery negative electrode slurry and lithium-ion battery negative electrode

By using a highly tough aqueous binder with flexible and rigid monomer coexisting in lithium-ion batteries, the problems of incomplete electrode structure and expansion of silicon-based negative electrodes are solved, and the electrochemical stability and cyclic stability are improved.

CN116515032BActive Publication Date: 2025-02-07WESTERN METAL MATERIAL
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310512314.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-09
Publication Date
2025-02-07
Estimated Expiration
2043-05-09

AI Technical Summary

Technical Problem

Existing water-based binders can easily lead to incomplete electrode structure under high surface loads and cannot effectively restrict the expansion of silicon particles in the silicon-based negative electrode, affecting the cycle life of the battery.

Method used

A high-tough aqueous binder coexisting with flexible monomers and rigid monomers is prepared by polymerization reaction, combining excellent mechanical properties and adhesive ability to alleviate the internal stress caused by the expansion of silicon particles in the silicon-based negative electrode.

Benefits of technology

Maintain the integrity of the electrode structure under high surface load, significantly improve the electrochemical stability and cyclic stability of lithium-ion batteries, and the capacity retention rate reaches more than 92%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116515032B_ABST
    Figure CN116515032B_ABST
Patent Text Reader

Abstract

The present invention provides a high-toughness water-based binder and a preparation method and application thereof, a lithium-ion battery negative electrode slurry and a lithium-ion battery negative electrode, and relates to the technical field of lithium-ion batteries. The raw materials for preparing the high-toughness water-based binder provided by the present invention include flexible monomers and rigid monomers; the flexible monomers include one or more of 2-ethylhexyl acrylate, 2-methoxyethyl acrylate, ethyl acrylate, butyl acrylate and isooctyl acrylate; the rigid monomers include one or more of styrene, methyl methacrylate, acrylonitrile and acrylic acid. The high-toughness water-based binder provided by the present invention has excellent adhesion and flexibility, can avoid cracking and powdering of electrode pole pieces, and can alleviate the internal stress generated by the expansion of active materials, effectively inhibit the collapse of the electrode structure caused by the fragmentation of active materials, maintain the integrity of the electrode structure, and improve the electrochemical stability of lithium-ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a high-toughness aqueous binder, a preparation method and application thereof, a lithium ion battery negative electrode slurry and a lithium ion battery negative electrode. Background Art

[0002] With the rapid development of the new energy industry, the battery industry, as the upstream supply chain of new energy, is in an important period of development opportunities. Lithium battery binder is one of the most important auxiliary materials in the lithium-ion battery manufacturing system, and plays an irreplaceable role in the electrode manufacturing process. The binder acts on the electrode, binds the active material, conductive additive and current collector, maintains the electronic contact between them, stabilizes the electrode plate structure, and has a significant impact on the normal use and cycle life of lithium-ion batteries.

[0003] Lithium-ion battery binders are mainly divided into two categories: one is oil-soluble binders with organic solvents as dispersants, and the other is water-based binders with water as dispersants. With the introduction of new green chemical concepts, water-based binders that are cheaper, more environmentally friendly, and have equally excellent performance have become the mainstream choice for lithium-ion battery binders, especially in negative electrodes.

[0004] Currently, there are still some problems with commercial water-based binders. On the one hand, electrode curling or falling off may occur at high surface loading, resulting in incomplete electrode structure and affecting battery cycle life. On the other hand, it is impossible to restrain the expansion of silicon particles in high energy density silicon-based negative electrodes and improve the service life of silicon-based negative electrodes. Summary of the invention

[0005] The purpose of the present invention is to provide a high-toughness aqueous binder and a preparation method and application thereof, a lithium-ion battery negative electrode slurry and a lithium-ion battery negative electrode. The high-toughness aqueous binder provided by the present invention can maintain the integrity of the electrode structure under high surface loading and can alleviate the internal stress generated by the expansion of silicon particles for silicon-based negative electrodes, effectively inhibit the collapse of the electrode structure caused by the fragmentation of silicon particles, maintain the integrity of the electrode structure, and improve the electrochemical stability of lithium-ion batteries.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a high-toughness water-based binder, wherein the raw materials for preparing the high-toughness water-based binder include a flexible monomer and a rigid monomer;

[0008] The flexible monomer includes one or more of 2-ethylhexyl acrylate, 2-methoxyethyl acrylate, ethyl acrylate, butyl acrylate and isooctyl acrylate; the rigid monomer includes one or more of styrene, methyl methacrylate, acrylonitrile and acrylic acid.

[0009] Preferably, the molar ratio of the flexible monomer to the rigid monomer is 5-9:1-5.

[0010] The present invention provides a method for preparing the high-toughness water-based binder described in the above technical solution, comprising the following steps:

[0011] Mixing a flexible monomer, a rigid monomer, a first emulsifier, a first initiator and water to obtain a monomer pre-emulsion;

[0012] The monomer pre-emulsion is mixed with a reaction base liquid containing a second emulsifier, a second initiator and water, and a polymerization reaction is carried out to obtain a high-toughness water-based adhesive.

[0013] Preferably, the total concentration of the flexible monomer and the rigid monomer in the monomer pre-emulsion is 20-70 wt. %; the concentration of the first emulsifier is 0.1-1 wt. %; and the concentration of the first initiator is 0.01-1 wt. %.

[0014] Preferably, the mass of the second emulsifier is 0.1-1 wt.% of the reaction base liquid; the mass of the second initiator is 0.01-1 wt.% of the reaction base liquid.

[0015] Preferably, the polymerization reaction temperature is 60-80° C., and the polymerization reaction time is 3-10 h.

[0016] The present invention provides the use of the high-toughness aqueous binder described in the above technical solution or the high-toughness aqueous binder prepared by the preparation method described in the above technical solution in negative electrode materials for lithium-ion batteries.

[0017] The present invention provides a lithium ion battery negative electrode slurry, comprising an active material, a conductive additive, a dispersant and a binder; the binder is the high-toughness aqueous binder described in the above technical solution or the high-toughness aqueous binder prepared by the preparation method described in the above technical solution.

[0018] Preferably, the mass ratio of the active material, the conductive additive, the dispersant and the binder is 92-95:2-1:2-1:4-1.

[0019] The present invention provides a lithium ion battery negative electrode, comprising a current collector and a lithium ion battery negative electrode material attached to the current collector; the lithium ion battery negative electrode material is obtained by coating the lithium ion battery negative electrode slurry described in the above technical solution on the current collector and drying it.

[0020] The present invention provides a high-toughness water-based binder, and the raw materials for preparing the high-toughness water-based binder include flexible monomers and rigid monomers; the flexible monomers include one or more of 2-ethylhexyl acrylate, 2-methoxyethyl acrylate, ethyl acrylate, butyl acrylate and isooctyl acrylate; the rigid monomers include one or more of styrene, methyl methacrylate, acrylonitrile and acrylic acid. Flexible segments and rigid segments coexist in the molecular chain of the high-toughness water-based binder provided by the present invention. In the present invention, the presence of the acrylic ester flexible segment can ensure that the binder has a certain toughness, and the formed slurry is not prone to cracking after drying. The presence of the rigid segment can ensure that the binder has a certain strength, ensure the stability of the electrode structure when the active material expands, and make the binder not easy to swell in the electrolyte. In addition, both the flexible segment and the rigid segment have polar groups, which ensure the strong adhesion between the binder and the active particles and the conductive agent. The high-toughness aqueous binder provided by the present invention has good stability and adhesion at high temperatures. When applied to silicon-based negative electrode materials, when the volume of silicon expands, the excellent mechanical properties and excellent adhesion ability of the binder can ensure the stability of the electrode structure and the integrity of the conductive network under high surface loading, without cracking the electrode, thereby improving the electrochemical stability of the battery.

[0021] The present invention provides a method for preparing the high-toughness water-based adhesive described in the above technical solution. The preparation method provided by the present invention is green, environmentally friendly, simple and easy to implement. The obtained adhesive has good stability and strong adhesion, and is suitable for large-scale preparation.

[0022] The present invention provides the application of the high-toughness water-based binder described in the above technical solution or the high-toughness water-based binder prepared by the preparation method described in the above technical solution in the negative electrode material of a lithium-ion battery. The binding force of the components in the negative electrode of the lithium-ion battery using the high-toughness water-based binder is strong. The high-toughness water-based binder can maintain the integrity of the electrode structure at a high surface load without cracking through excellent mechanical properties and bonding ability, and can effectively alleviate the stress generated by the expansion of silicon-based materials during the cycle, significantly improving the cycle stability of the lithium-ion battery. The results of the embodiment show that the capacity retention rate of the lithium-ion battery prepared by the high-toughness water-based binder provided by the present invention is still above 92% after 150 cycles. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a comparison chart of the peeling strength of lithium ion battery electrode sheets using the binder of Example 1 and Comparative Example 1;

[0024] Figure 2 The figure is a comparison chart of the cycle performance of lithium ion half-cells using the binders of Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0025] The present invention provides a high-toughness water-based binder, wherein the raw materials for preparing the high-toughness water-based binder include a flexible monomer and a rigid monomer;

[0026] The flexible monomer includes one or more of 2-ethylhexyl acrylate, 2-methoxyethyl acrylate, ethyl acrylate, butyl acrylate and isooctyl acrylate; the rigid monomer includes one or more of styrene, methyl methacrylate, acrylonitrile and acrylic acid.

[0027] In the present invention, the flexible segments and the rigid segments coexist in the molecular chain of the high-toughness water-based binder.

[0028] In the present invention, the molar ratio of the flexible monomer to the rigid monomer is preferably 5-9:1-5, more preferably 1-2:1.

[0029] In the present invention, the presence of the flexible segment can ensure that the binder has a certain toughness, and the formed slurry is not prone to cracking after drying. The presence of the rigid segment can ensure that the binder has a certain strength, ensure the stability of the electrode structure when the active material expands, and make the binder not easy to swell in the electrolyte. In addition, both the flexible segment and the rigid segment have polar groups, which ensure the strong adhesion between the binder and the active particles and the conductive agent. The high-toughness aqueous binder provided by the present invention can enable the silicon-based negative electrode to maintain good stability and adhesion under high loads, and when the Si / C negative electrode using the binder is assembled into a battery, it exhibits excellent electrochemical performance. The present invention limits the molar ratio of flexible monomers to rigid monomers to 5 to 9: 1 to 5. Within the above range, the comprehensive performance of the binder can be improved.

[0030] The present invention provides a method for preparing the high-toughness water-based binder described in the above technical solution, comprising the following steps:

[0031] Mixing a flexible monomer, a rigid monomer, a first emulsifier, a first initiator and water to obtain a monomer pre-emulsion;

[0032] The monomer pre-emulsion is mixed with a reaction base liquid containing a second emulsifier, a second initiator and water, and a polymerization reaction is carried out to obtain a high-toughness water-based adhesive.

[0033] The present invention mixes a flexible monomer, a rigid monomer, a first emulsifier, a first initiator and water to obtain a monomer pre-emulsion. In the present invention, the total concentration of the flexible monomer and the rigid monomer in the monomer pre-emulsion is preferably 20-70wt.%, more preferably 33wt.%; the concentration of the first emulsifier is preferably 0.1-1wt.%, more preferably 0.5-0.8wt.%; the concentration of the first initiator is preferably 0.01-1wt.%, more preferably 0.07-0.1wt.%. In the present invention, the mixing of the flexible monomer, the rigid monomer, the first emulsifier, the first initiator and water preferably includes: dropping the mixture of the flexible monomer and the rigid monomer into the dispersion of the first emulsifier, the first initiator and water. In the present invention, the rate of the dropping is preferably 5-50mL / h, more preferably 10mL / h.

[0034] In the present invention, the flexible monomer includes one or more of 2-ethylhexyl acrylate, 2-methoxyethyl acrylate, ethyl acrylate, butyl acrylate and isooctyl acrylate; the rigid monomer includes one or more of styrene, methyl methacrylate, acrylonitrile and acrylic acid; the molar ratio of the flexible monomer to the rigid monomer is preferably 5-9:1-5, more preferably 1-2:1. In the present invention, the first emulsifier preferably includes one or more of sodium dodecylbenzene sulfonate (SDBS), sodium dodecyl sulfate (SDS), peregal O-9, peregal OS-15 and emulsifier OP-10. In the present invention, the first initiator preferably includes one or more of ammonium persulfate and potassium persulfate. In the present invention, the water is preferably deionized water.

[0035] After obtaining the monomer pre-emulsion, the present invention mixes the monomer pre-emulsion with a reaction base liquid containing a second emulsifier, a second initiator and water, and performs a polymerization reaction to obtain a high-toughness water-based binder. In the present invention, the mass of the second emulsifier is preferably 0.1-1wt.% of the reaction base liquid, and more preferably 0.5-0.8wt.%; the mass of the second initiator is preferably 0.01-1wt.% of the reaction base liquid, and more preferably 0.07-0.1wt.%. In the present invention, the mass ratio of the monomer pre-emulsion to the reaction base liquid is preferably 1-3:3-1, and more preferably 1.5:1.

[0036] In the present invention, the mixing of the monomer pre-emulsion and the reaction base liquid containing the second emulsifier, the second initiator and water preferably comprises: dropping the monomer pre-emulsion into the reaction base liquid containing the second emulsifier, the second initiator and water. In the present invention, the dropping rate is preferably 5 to 50 mL / h, more preferably 10 mL / h.

[0037] In the present invention, the second emulsifier preferably includes one or more of sodium dodecylbenzene sulfonate (SDBS), sodium dodecyl sulfate (SDS), peregal O-9, peregal OS-15 and emulsifier OP-10. In the present invention, the second initiator preferably includes one or more of ammonium persulfate and potassium persulfate. In the present invention, the water is preferably deionized water.

[0038] In the present invention, the polymerization reaction temperature is preferably 60-80°C, more preferably 70°C; the polymerization reaction time is preferably 3-10h, more preferably 5h. In the present invention, the polymerization reaction is preferably carried out in a protective atmosphere, more preferably a nitrogen atmosphere.

[0039] The present invention provides the use of the high-toughness aqueous binder described in the above technical solution or the high-toughness aqueous binder prepared by the preparation method described in the above technical solution in the negative electrode material of lithium-ion batteries, preferably in silicon-based negative electrode materials. The high-toughness aqueous binder provided by the present invention enables the silicon-based negative electrode material to maintain good stability and adhesion under high load, and when the silicon negative electrode using the high-toughness aqueous binder is assembled into a button battery, it exhibits excellent electrochemical performance.

[0040] The present invention provides a lithium ion battery negative electrode slurry, comprising an active material, a conductive additive, a dispersant and a binder; the binder is the high-toughness aqueous binder described in the above technical solution or the high-toughness aqueous binder prepared by the preparation method described in the above technical solution.

[0041] In the present invention, the mass ratio of the active material, the conductive additive, the dispersant and the binder is preferably 92-95: 2-1: 2-1: 4-1. In the present invention, the active material preferably includes one or more of silicon material, silicon-carbon material, silicon-oxygen material and graphite; the conductive additive preferably includes one or more of Super P, acetylene black and Ketjen black; the dispersant is preferably sodium carboxymethyl cellulose (CMC).

[0042] In the present invention, the method for preparing the negative electrode slurry of the lithium ion battery preferably comprises: mixing the active material, the conductive additive, the dispersant and the binder, and dispersing them in water by stirring to obtain the negative electrode slurry of the lithium ion battery. In the present invention, the water is preferably deionized water. In the present invention, the solid content of the negative electrode slurry of the lithium ion battery is preferably 30 to 55 wt.%, more preferably 40 wt.%.

[0043] The present invention provides a lithium-ion battery negative electrode, comprising a current collector and a lithium-ion battery negative electrode material attached to the current collector; the lithium-ion battery negative electrode material is obtained by coating the lithium-ion battery negative electrode slurry described in the above technical solution on the current collector and drying it. In the present invention, the coating thickness of the lithium-ion battery negative electrode slurry on the current collector is preferably 200 to 400 microns. In the present invention, the current collector preferably comprises copper foil. In the present invention, the thickness of the current collector is preferably 8 microns. In the present invention, the coating is preferably carried out using an automatic coating machine. In the present invention, the drying is preferably vacuum drying.

[0044] In the present invention, the negative electrode of the lithium-ion battery is preferably a negative electrode sheet with a diameter of 12 mm.

[0045] The present invention also provides a lithium-ion battery, comprising the lithium-ion battery negative electrode described in the above technical solution. In the present invention, the preparation method of the lithium-ion battery preferably includes the following steps: placing the lithium-ion battery negative electrode in a glove box filled with argon gas to assemble into a 2016 button half-cell; using a pure lithium sheet as a counter electrode and Celgard 2300 as a diaphragm; the electrolyte uses a mixed solution of ethylene carbonate (EC) and diethyl carbonate (DEC) (the volume ratio of EC and DEC is 1:1) containing 1 mol / L lithium hexafluorophosphate (LiPF6), and adding 5% volume fraction of fluoroethylene carbonate (FEC) to obtain a lithium-ion battery.

[0046] The high-toughness aqueous binder provided by the present invention has excellent adhesion and flexibility, can avoid cracking and powdering of electrode plates, and can relieve the internal stress generated by the expansion of active materials, effectively inhibit the collapse of the electrode structure caused by the fragmentation of active materials, maintain the integrity of the electrode structure, and improve the electrochemical stability of lithium-ion batteries.

[0047] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0048] Example 1

[0049] (1) Dispersing 0.08 g of emulsifier SDS and OP-10 and 0.02 g of initiator potassium persulfate in 20 g of deionized water, stirring until uniform, and dropping 10 g of a mixed monomer of 2-ethylhexyl acrylate and acrylonitrile (the molar ratio of 2-ethylhexyl acrylate to acrylonitrile is 2:1) into the above dispersion at a high speed dispersion rate of 10 mL / h, and continuing stirring for 30 min to obtain a monomer pre-emulsion;

[0050] (2) Take 0.08 g of emulsifier SDS and OP-10 respectively and 0.02 g of initiator potassium persulfate and disperse them in 20 g of deionized water, stir until uniform, raise the temperature to 70° C. under nitrogen protection, add the monomer pre-emulsion dropwise at a rate of 10 mL / h, react for 5 h to obtain a white emulsion, and obtain a high-toughness water-based binder.

[0051] Comparative Example 1

[0052] Styrene butadiene rubber (SBR) is used as comparative example 1.

[0053] Test Case

[0054] Toughness test: The high-toughness water-based binder prepared in Example 1 and the SBR casting film of Comparative Example 1 were dried and subjected to toughness test. The toughness test was carried out according to GB / T41932-2022 "Fire Toughness of Plastics (G IC and K IC ) is determined by the linear elastic fracture mechanics (LEFM) method, with the critical stress intensity factor K IC The size of the fracture toughness of the material is measured, and the test results are shown in Table 1.

[0055] Bond strength and electrochemical performance tests:

[0056] (1) A negative electrode active material (a mixture of SiO / C and graphite, with a theoretical specific capacity of 550 mAh / g), a conductive additive (SuperP), a dispersant (CMC) and a binder are mixed in a mass ratio of 95:2:1.5:1.5, and are uniformly dispersed in deionized water by stirring to obtain a uniformly mixed lithium ion battery negative electrode slurry with a solid content of 40 wt.%.

[0057] (2) The lithium-ion battery negative electrode slurry in (1) is uniformly coated on a copper foil 8 μm thick using an automatic coating machine to a coating thickness of 250 μm, and then placed in a vacuum drying oven to dry and remove the solvent; after drying, it is cut into negative electrode sheets with a diameter of 12 mm.

[0058] (3) The negative electrode sheet prepared in (2) was transferred to a glove box filled with argon and assembled into a 2016 button half-cell; a pure lithium sheet was used as the counter electrode and Celgard 2300 was used as the separator; the electrolyte was a mixed solution of ethylene carbonate (EC) and diethyl carbonate (DEC) (the volume ratio of EC and DEC was 1:1) containing 1 mol / L lithium hexafluorophosphate (LiPF6), and 5% by volume of fluoroethylene carbonate (FEC) was added.

[0059] (4) The button cell assembled in (3) was left to stand for 6 h, and then cycled at a rate of 0.1 C for one cycle in the voltage range of 0.01 to 2.00 V, and then charged and discharged at a rate of 0.5 C.

[0060] The high-toughness aqueous binder prepared in Example 1 and the SBR in Comparative Example 1 were used as binders to prepare negative electrode sheets of lithium-ion batteries. The adhesion strength of the electrodes was tested using a 180° peel test. The obtained peel strength comparison diagram is shown in FIG. Figure 1 As shown. Figure 1 It can be seen that with SBR binder (100N·m -1 ), the electrode prepared with high-toughness aqueous binder has a stronger bonding strength of 180N·m -1 .

[0061] The high-toughness aqueous binder prepared in Example 1 and the SBR prepared in Comparative Example 1 were used as binders for the negative electrode and assembled into a 2016 button-type half-cell. The electrochemical performance of the cell was tested. The results are shown in Table 2. The cycle performance comparison diagram is shown in Table 2. Figure 2 As shown. Figure 2 It can be seen that when the electrode surface loading is 12 mg cm -2 The electrode using the high-toughness aqueous binder has a high capacity retention rate of 92.7% at a current density of 0.5 C. By comparison, at a high surface loading, the high-toughness aqueous binder prepared by the present invention has a higher cycle stability than the SBR binder.

[0062] Example 2

[0063] (1) Dispersing 0.08 g of emulsifier SDS and OP-10 and 0.02 g of initiator potassium persulfate in 20 g of deionized water, stirring until uniform, and dropping 10 g of 2-ethylhexyl acrylate and acrylic acid mixed monomer (the molar ratio of 2-ethylhexyl acrylate to acrylic acid is 1:1) into the above dispersion at a high speed dispersion rate of 10 mL / h, and continuing stirring for 30 min to obtain a monomer pre-emulsion;

[0064] (2) Take 0.08 g of emulsifier SDS and OP-10 and 0.02 g of potassium persulfate respectively and disperse them in 20 g of deionized water, stir until uniform, raise the temperature to 70° C. under nitrogen protection, add the monomer pre-emulsion dropwise at a rate of 10 mL / h, react for 5 h to obtain a white emulsion, and obtain a high-toughness water-based binder.

[0065] The critical stress intensity factor K of the high-toughness water-based binder is tested by the test example method. IC To characterize its toughness, the results are shown in Table 1.

[0066] The high-toughness aqueous binder was applied to the negative electrode and assembled into a 2016 button-type half-cell using the method of the test example to test the electrochemical performance. The results are shown in Table 2.

[0067] Example 3

[0068] (1) Dispersing 0.08 g of emulsifier SDS and OP-10 and 0.02 g of initiator potassium persulfate in 20 g of deionized water, stirring until uniform, and dropping 10 g of butyl acrylate and acrylonitrile mixed monomer (the molar ratio of butyl acrylate to acrylonitrile is 1:1) into the above dispersion at a high speed dispersion rate of 10 mL / h, and continuing stirring for 30 min to obtain a monomer pre-emulsion;

[0069] (2) Take 0.08 g of emulsifier SDS and OP-10 and 0.02 g of potassium persulfate respectively and disperse them in 20 g of deionized water, stir until uniform, raise the temperature to 70° C. under nitrogen protection, add the monomer pre-emulsion dropwise at a rate of 10 mL / h, react for 5 h to obtain a white emulsion, and obtain a high-toughness water-based binder.

[0070] The critical stress intensity factor K of the high-toughness water-based binder is tested by the test example method. IC To characterize its toughness, the results are shown in Table 1.

[0071] The high-toughness aqueous binder was applied to the negative electrode and assembled into a 2016 button-type half-cell using the method of the test example to test the electrochemical performance. The results are shown in Table 2.

[0072] Example 4

[0073] (1) Dispersing 0.08 g of emulsifier SDS and OP-10 and 0.02 g of initiator potassium persulfate in 20 g of deionized water, stirring until uniform, and dropping 10 g of a mixed monomer of 2-methoxyethyl acrylate and acrylonitrile (the molar ratio of 2-methoxyethyl acrylate to acrylonitrile is 2:1) into the above dispersion at a high speed dispersion rate of 10 mL / h, and continuing stirring for 30 min to obtain a monomer pre-emulsion;

[0074] (2) Take 0.08 g of emulsifier SDS and OP-10 and 0.02 g of potassium persulfate respectively and disperse them in 20 g of deionized water, stir until uniform, raise the temperature to 70° C. under nitrogen protection, add the monomer pre-emulsion dropwise at a rate of 10 mL / h, react for 5 h to obtain a white emulsion, and obtain a high-toughness water-based binder.

[0075] The critical stress intensity factor K of the high-toughness water-based binder is tested by the test example method. IC To characterize its toughness, the results are shown in Table 1.

[0076] The high-toughness aqueous binder was applied to the negative electrode and assembled into a 2016 button-type half-cell using the method of the test example to test the electrochemical performance. The results are shown in Table 2.

[0077] Example 5

[0078] (1) Disperse 0.08 g of emulsifier SDS and OP-10 and 0.02 g of initiator potassium persulfate in 20 g of deionized water, stir until uniform, and drop 10 g of a mixed monomer of isooctyl acrylate and styrene (the molar ratio of isooctyl acrylate to styrene is 1:1) into the above dispersion at a high speed dispersion rate of 10 mL / h. Continue stirring for 30 min to obtain a monomer pre-emulsion;

[0079] (2) Take 0.08 g of emulsifier SDS and OP-10 and 0.02 g of potassium persulfate respectively and disperse them in 20 g of deionized water, stir until uniform, raise the temperature to 70° C. under nitrogen protection, add the monomer pre-emulsion dropwise at a rate of 10 mL / h, react for 5 h to obtain a white emulsion, and obtain a high-toughness water-based binder.

[0080] The critical stress intensity factor K of the high-toughness water-based binder is tested by the test example method. IC To characterize its toughness, the results are shown in Table 1.

[0081] The high-toughness aqueous binder was applied to the negative electrode and assembled into a 2016 button-type half-cell using the method of the test example to test the electrochemical performance. The results are shown in Table 2.

[0082] Table 1 Critical stress intensity factor test data of Examples 1 to 5 and Comparative Example 1

[0083] serial number <![CDATA[Critical stress intensity factor K IC (MPa·m 1 / 2 )]]> Example 1 84.7 Example 2 89.2 Example 3 78.3 Example 4 91.3 Example 5 89.7 Comparative Example 1 23.7

[0084] It can be seen from Table 1 that with SBR binder (23.7MPa·m 1 / 2 ), the high-toughness water-based binder prepared by the present invention has a higher critical stress intensity factor, that is, higher toughness.

[0085] Table 2 Electrochemical cycle performance data of Examples 1 to 5 and Comparative Example 1

[0086]

[0087]

[0088] From the results in Table 2, it can be seen that the high-toughness water-based binder provided by the present invention has a surface loading of 12 mg / cm 2When the coulomb efficiency of the thick electrode is 88% or more in the first cycle, the capacity retention rate after 150 cycles is 92% or more. However, the coulomb efficiency of the binder SBR in comparative example 1 is 85.58% in the first cycle, and the capacity retention rate after 150 cycles is only 76.8%. It can be seen that the high-toughness water-based binder of the present invention can still maintain the cycle stability of silicon-based negative electrode materials at high surface loading.

[0089] The high-toughness aqueous binder provided by the present invention can effectively relieve the stress generated between silicon-based material particles during the cycle through excellent mechanical properties and bonding ability, and significantly improve the cycle stability of lithium-ion batteries. The high-toughness aqueous binder provided by the present invention is water-soluble, green and environmentally friendly, and its structure is easy to control, which can well meet the requirements of silicon-based or other negative electrode preparation and production.

[0090] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a high-toughness water-based binder, comprising the following steps: A flexible monomer, a rigid monomer, a first emulsifier, a first initiator and water are mixed to obtain a monomer pre-emulsion; the first emulsifier is sodium dodecyl sulfate and OP-10; the first initiator is potassium persulfate; when the flexible monomer is 2-ethylhexyl acrylate, the rigid monomer is acrylic acid, and the molar ratio of the 2-ethylhexyl acrylate to the acrylic acid is 1:1; when the flexible monomer is 2-methoxyethyl acrylate, the rigid monomer is acrylonitrile, and the molar ratio of the 2-methoxyethyl acrylate to the acrylonitrile is 2:1; when the flexible monomer is isooctyl acrylate, the rigid monomer is styrene, and the molar ratio of the isooctyl acrylate to the styrene is 1:1; the total concentration of the flexible monomer and the rigid monomer in the monomer pre-emulsion is 33wt.%; The monomer pre-emulsion is added dropwise to a reaction base liquid containing a second emulsifier, a second initiator and water to carry out a polymerization reaction to obtain a high-toughness water-based binder; the second emulsifier is sodium dodecyl sulfate and OP-10; the second initiator is potassium persulfate; the mass ratio of the monomer pre-emulsion to the reaction base liquid is 1.5:

1.

2. The preparation method according to claim 1, characterized in that: The concentration of the first emulsifier in the monomer pre-emulsion is 0.1-1 wt. %; the concentration of the first initiator is 0.01-1 wt. %.

3. The preparation method according to claim 1, characterized in that: The mass of the second emulsifier is 0.1-1 wt.% of the reaction base liquid; the mass of the second initiator is 0.01-1 wt.% of the reaction base liquid.

4. The preparation method according to claim 1, characterized in that: The polymerization reaction temperature is 60-80° C., and the polymerization reaction time is 3-10 hours.

5. Use of the high-toughness aqueous binder prepared by the preparation method according to any one of claims 1 to 4 in negative electrode materials for lithium-ion batteries.

6. A negative electrode slurry for a lithium ion battery, characterized in that: The invention comprises active materials, conductive additives, dispersants and binders; the binder is a high-toughness water-based binder prepared by the preparation method according to any one of claims 1 to 4.

7. The negative electrode slurry for lithium-ion batteries according to claim 6, characterized in that: The mass ratio of the active material, the conductive additive, the dispersant and the binder is 92-95:2-1:2-1:4-1.

8. A lithium ion battery negative electrode, comprising a current collector and a lithium ion battery negative electrode material attached to the current collector; the lithium ion battery negative electrode material is obtained by coating the lithium ion battery negative electrode slurry according to any one of claims 6 to 7 on the current collector and drying it.

Citation Information

Patent Citations

  • Aqueous adhesive for lithium ion secondary battery

    CN103509500A